On Weak Forms of Open and Closed Functions via $(τ_1,τ_2)β$-open Sets (European Journal of Pure and Applied Mathematics, 2025)
This paper is concerned with the concepts of weakly $(τ_1,τ_2)β$-open functions and weakly $(τ_1,τ_2)β$-closed functions. Furthermore, several characterizations of weakly $(τ_1,τ_2)β$-open functions and weakly $(τ_1,τ_2)$-closed functions are investigated.
Keywords: weakly $(τ_1,τ_2)β$-open function; weakly $(τ_1,τ_2)β$-closed function